Enriching the content of extracurricular activities in universities with the ideas of interactive learning (Pedagogy of Higher and Secondary Education, 2021)
The author reveals the problem of forming a willingess to primary school teachers to use interactive learning technologies and enrich extracurricular work in high school ideas of interactive learning.
Keywords: readiness to use online learning technologies; interactive technologies; content extracurricular work at the university